Epidemiological study of shigellosis in an urban area of Argentina - Florencia Rolfo; Gustavo Horacio Marin; Martin Silberman; Jorgelina Pattin; Silvina Giugnio; Blanca Gatti; Marisa Bettiol; Ana Rigoni (Journal of Infection in Developing Countries)
Introduction: Shigellosis represents one of the main causes of bloody diarrhoea in South America. This study aimed to establish the incidence of shigellosis in an urban zone of Buenos Aires, Argentina, by examining the type of Shigella and living conditions associated with this infection.